German social democracy, 1905-1917 : the development of the great schism - Schorske, Carl E. (Cambridge : Harvard University Press, 1983)
Bibliotheek François Vercammen
Engels
Monografie
Keywords: Sozialdemokratische Partei Deutschlands (SPD).; Duitsland